(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the banking industry, digital transformation is a continual process that impacts both the external and internal environments by revamping internal procedures and current systems. There are numerous reasons for digital transformation, such as serving remote areas without physical branches, differentiating from competitors, or lowering operating costs. In any event, there are many reservations regarding digital technology’s acceptability. In recent years, digitization has engulfed nearly the whole globe. Because e-service quality and consumer loyalty towards e-commerce websites are regarded as the most influential factors in internet marketing, a thorough evaluation of E-service quality and consumer loyalty is required for any type of industry. As a result, the banking industry could not be left behind. Cashless banking is the necessity of the hour, and all institutions must catch up. A private sector leader seeking to provide ’World Class Banking,’ has introduced many digital banking services such as online banking, payzapp, chillr, and so on. But, in order to pique the market’s attention, it is necessary to develop a strong digital footprint in the market, which is the topic of this research study. This report is based on an empirical investigation to determine people’s knowledge and preference for banking products especially e-services